Longitudinal study of patients after surgical treatment for cervical lesions: detection of HPV DNA and prevalence of HPV-specific antibodies - Tachezy, Ruth; Adlerová, Iva; Ludvíková, Viera; Rob, Lukáš; Kučera, Tomáš; Slavík, Vítězslav; Beková, Alena; Robová, Helena; Pluta, Marek; Hamšíková, Eva (European journal of clinical microbiology & infectious diseases, 2006)
The principal aims of this study were to test whether persistence of human papillomavirus (HPV) DNA is predictive of recurrent disease in women after surgical treatment for cervical lesions, to distinguish between persistent and newly acquired HPV infection, and to observe the effect of surgical treatment on levels of HPV-specific antibodies. A group of 198 patients surgically treated for low-grade and high-grade squamous intraepithelial lesions and 35 age-matched controls were monitored for 18 months at 6-month intervals. The presence of HPV DNA in cervical smears was detected by means of consensus polymerase chain reaction, and serum levels of HPV-specific antibodies to HPV types 16, 18, 31, 33, and 45 were measured. In ten patients positive for HPV type 16 in consecutive samples, the HPV 16 variants were identified using a polymerase chain reaction specific for the long control region. Data regarding demographics, risk factors for cervical cancer, and risks related to HPV exposure were collected through a patient questionnaire. Subjects persistently positive for HPV DNA were more likely to present with cytological and/or colposcopical abnormalities. A higher reactivity to HPV-specific antibodies was observed in these women at the 18-month follow-up visit. All ten patients with HPV 16 infection detected in consecutive samples showed persistence of either the same prototype or the same variant during the follow-up period. Risky sexual behavior and smoking were more common in patients than in controls. Persistent HPV infection as demonstrated by both HPV DNA detection and antibody detection appears to be a risk factor for the recurrence of pathological findings in women after surgery. An individually based approach to surgical treatment is an important factor in the outcome of disease at follow-up.
Keywords: Follow-Up Studies; Financing, Organized; Human papillomavirus 16; DNA, Viral; protilátky virové; Humans; lidé; Antibodies, Viral; Prevalence; infekce onkogenními viry; následné studie; mladiství; lidé středního věku; Papillomaviridae; financování organizované; prevalence; Middle Aged; longitudinální studie; Female; Uterine Cervical Neoplasms; Adult; Longitudinal Studies; Papillomavirus Infections; Aged; Uterine Cervical Diseases; nemoci cervix uteri; infekce papilomavirem; ženské pohlaví; Tumor Virus Infections; DNA virů; dospělí; lidský papilomavirus 16; nádory děložního čípku; Adolescent; senioři